2009
DOI: 10.1111/j.1439-0434.2009.01559.x
|View full text |Cite
|
Sign up to set email alerts
|

A Model‐based Assessment of the Impacts of Climate Variability on Fusarium Head Blight Seasonal Risk in Southern Brazil

Abstract: The frequency of Fusarium head blight (FHB) outbreaks increased considerably in many countries in the last two decades. We used a crop-disease model to assess the impacts of climate variability over a 50-year period at Passo Fundo, Rio Grande do Sul, Brazil. Thirty individual simulation runs of a wheat model were performed for each year by varying planting dates from 1 June to 30 June. For each simulation, an FHB risk index was estimated with the disease model using the heading date simulated by the crop model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 26 publications
4
43
0
1
Order By: Relevance
“…Coincidently, the ENSO phases in each period corresponded to "neutral," "warm," and "cold," respectively. This is in agreement with reports [9] that FHB epidemics are likely to be more severe in "neutral" and "warm" than in the "cold" phase, in this part of the world. The model constructed with the data between September 15 and October 15 in 2008, 2009, and 2010, respectively, was used to predict the density of G. zeae spores in the air of Passo Fundo.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Coincidently, the ENSO phases in each period corresponded to "neutral," "warm," and "cold," respectively. This is in agreement with reports [9] that FHB epidemics are likely to be more severe in "neutral" and "warm" than in the "cold" phase, in this part of the world. The model constructed with the data between September 15 and October 15 in 2008, 2009, and 2010, respectively, was used to predict the density of G. zeae spores in the air of Passo Fundo.…”
Section: Resultssupporting
confidence: 82%
“…In Brazil, similar to other parts of the world, an increasing frequency of severe FHB outbreaks has been reported over the last two decades (especially after 1990) resulting in severe yield losses [1,8,9]. No wheat varieties are immune to FHB and resistance is generally controlled by several genes of moderate/weak effect and they are defined genetically as quantitative trait loci (QTL).…”
Section: Introductionmentioning
confidence: 99%
“…The DON levels determined in our study are in agreement with previous reports in the country, using chromatography methods. However, year-to-year (or decades) and region-to-region variations are expected, given the strong dependence on seasonal weather conditions as well as management practices that contribute to suppress the disease and mycotoxin levels (Del Ponte et al, 2009). For example, Furlong et al (1995), two decades earlier, analyzed 38 samples of commercial wheat grain and found DON in 55 % of the samples, but at lower mean and range (400 to 590 µg kg ) found in this study, including all samples.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Fusarium causes some of the most economically damaging plant diseases, affecting viticulture as well as other plant species throughout the world (Del Ponte et al, 2009;Matos et al, 2009). In grapes, Fusarium, mainly the species Fusarium oxysporum f. sp herbemontis, penetrates into root tissues, which can lead to plant death .…”
Section: Introductionmentioning
confidence: 99%